In Vitro Susceptibility of Candida Species to Four Antifungal Agents Assessed by the Reference Broth Microdilution Method - Fahriye Eksi; Efgan Dogan Gayyurhan; Iclal Balci (The Scientific World Journal)
This study was performed to determine the distribution of Candida species isolated from the blood cultures of the patients hospitalized in our hospital and to investigate their antifungal susceptibility. Candida strains were identified at species level by using classical methods and API ID 32C (bioMerieux, France) identification kits. The susceptibility of the strains to amphotericin B, fluconazole, voriconazole, and caspofungin was evaluated by using the reference broth microdilution method in document M27-A3 of the Clinical and Laboratory Standards Institute. Of the 111 Candida strains isolated, 47.7% were identified as C. albicans and 52.3% as non-albicans Candida strains. The MIC ranges were 0.03–1 μg/mL for amphotericin B, 0.125–≥64 μg/mL for fluconazole, 0.03–16 μg/mL for voriconazole, and 0.015–0.25 μg/mL for caspofungin. All Candida strains were susceptible to amphotericin B and caspofungin. 10.8% isolates were resistant to fluconazole and 8.1% isolates were dose-dependent susceptible. While 0.9% isolate was resistant to voriconazole, 0.9% isolate was dose-dependent susceptible. In our study, C. albicans and C. parapsilosis were the most frequently encountered agents of candidemia and it was detected that voriconazole with a low resistance rate might also be used with confidence in the treatment of infections occurring with these agents, primarily besides amphotericin B and caspofungin.